(untitled) (Research, Society and Development, 2023)
Considering the adaptations in the educational scope made as a result of the pandemic condition associated with the SARS-CoV-2 microorganism, this work aims to evaluate the impact of the remote modality in higher education institutions during the current pandemic period. Therefore, a systematic literature review was carried out, associated with exclusion criteria that include theses, dissertations, or works published in annals and databases such as PubMed. Several public and private institutions have adopted pedagogical didactic strategies due to the widespread of COVID- 19, aiming to offer greater academic support to students due to the isolation measures required by government agents, generating changes in the conventional study environment, so as not to compromise the learning of students. higher education students. Among the main problems pointed out by the students who evaluated the remote modality, there is the impairment of concentration, learning difficulties, as well as the absence of an environment conducive to academic dedication. However, it appears that the pandemic state has brought about changes in higher education institutions, including the emergence of new problems such as the lack of autonomy in students in the learning aspect and the need to build methodologies aimed at engaging the student, enabling the continuity of the process pedagogical.